THE NEED FOR A NURSE MANAGER IN FAMILY HEALTH UNITS: A DESCRIPTIVE-EXPLORATORY STUDY - Irene Duarte Monteiro Pereira, Sandra; Maria Telo Pousa, Olga; Zulay Ferreira, Miriam; do Carmo Santiago, Maria (Health and Society, 2024)
The USF were a milestone of New Public Management (NGP) for their contribution to improving the economy and the quality of care. It is based on decentralized management, but includes coordination with the doctor identified in the application, losing the role of nurse manager close to the nursing team. This quantitative descriptive-exploratory study aimed to identify the advantages perceived by nurses regarding the advantages of a nurse manager in the USF. The nurses’ perception noted the need for a nurse manager in the USF with skills in the area of management, for service planning, conflict management, a leader who promotes team unity, professional development and class visualization.